Determination of Embedded Depth of Soldier Piles in Pile-Anchor Supporting System in Granite Residual Soil Area. (19th February 2021) - Liu, Yiao; Wang, Changming; Liu, Xiaoyang; Gao, Ruiyuan; Li, Bailong; Khan, Kaleem Ullah Jan
Abstract : Reasonable depth of pile embedment is one of the key factors for the success of deep foundation pit projects. This paper has taken a deep foundation pit project in a granite residual soil area in Shenzhen as an example and used physical model tests to study the deformation law of the piles and the surrounding soil during the excavation of the deep foundation pit, revealing the variation law of earth pressure in time and space in the pit and then verified it by numerical simulation. The influence of the embedded depth of the pile on the deformation and earth pressure of the deep foundation pit is then explicitly discussed. The study shows that the embedded depth has a significant effect on the deformation and earth pressure distribution of the foundation pit. The earth pressure in front of the pile tends to approach the passive earth pressure as the embedment depth decreases, while the earth pressure behind the pile is in between the Rankine active earth pressure and the static soil pressure; the settlement value and settlement range of the surrounding soil are doubled. The pile displacement increases as the maximum displacement point rises. The maximum displacement of the pile body was used as the basis for determining the instability of the foundation pit. The optimum embedded depth is obtained when the depth of embedment of the pile is 0.22 H (H is the excavation depth of the foundation pit).